Transition From Targeted Breeding to Mainstreaming of Biofortification Traits in Crop Improvement Programs - Virk, Parminder S.; Andersson, Meike S.; Arcos, Jairo; Govindaraj, Mahalingam; Pfeiffer, Wolfgang H. (Frontiers in Plant Science, 2021)
Biofortification breeding for the three important micronutrients for human health namely, iron (Fe), zinc (Zn) and provitamin A (PVA), has gained momentum in recent years. HarvestPlus along with its global consortium partners enhances Fe, Zn and PVA in staple crops. HarvestPlus’ strategic and applied research is driven by product-based impact pathway that integrates crop breeding, nutrition research, impact assessment, advocacy and communication to implement country-specific crop delivery plans. Targeted breeding has resulted in 393 biofortified crop varieties, by the end of 2020 which have been released or are in testing in 63 countries, potentially benefitting more than 48 million people. Nevertheless, to scale out to reach more than a billion people by 2030, future breeding lines are being distributed by CGIAR centers and submitted by National Agricultural Research System (NARS) to varietal release committees, should be biofortified. It is envisaged that biofortification traits mainstreaming will be driven by high-throughput micronutrient phenotyping, genomic selection coupled with speed breeding for accelerating genetic gains. It is noteworthy that targeted breeding gradually leads to mainstreaming as the latter capitalizes on the progress made in the former. Efficacy studies revealed the nutritional significance of Fe, Zn and PVA biofortified varieties over non-biofortified. Mainstreaming will ensure the integration of biofortified traits into competitive varieties and hybrids developed by private and public sector. Mainstreaming strategy has just been initiated in select Consultative Group for International Agricultural Research (CGIAR) centers namely, International Maize and Wheat Improvement Center (CIMMYT), International Rice Research Institute (IRRI), International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), International Institute of Tropical Agriculture (IITA) and International Center for Tropical Agriculture (CIAT). This review will present the key successes of targeted breeding and its relevance to the mainstreaming those would achieve scaling of biofortification to billions sustainably.